Pengaruh Ambiguitas Peran dan Beban Kerja Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum (PU) Kabupaten Dompu - Mustika Ratu; Ikbal Irawan; Amirul Mukminin (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to determine the effect of role ambiguity and workload on employee performance at the Dompu Regency Umin Works (PU) Department. This type of research is associative with the research sample being 105 employees. Data collection techniques in this research were observation, questionnaires and questionnaires. The data analysis technique uses multiple linear regression analysis. The research results show that role ambiguity and workload partially have a significant influence on employee performance. Simultaneously, role ambiguity and workload also have a significant influence on employee performance at the Dompu Regency Public Works (PU) Department.